Chemical Constituents from the Fruits of Lycium chinense - Song, Hong-Keun; Chung, Ill-Min; Lim, Jung-Dae; Ahmad, Ateeque (Asian Journal of Chemistry, 2013)
Five compounds viz., n-hexacos-5,8,11-trienoic acid (1), n-tridecanyl n-octadec-9,12-dienoate (2), n-triacont-11-enoic acid (3), n-eicosanoic acid (4), n-butyl octadec-9,12-dienoate (5) were isolated from the methanol extract of Lycium chinense fruits. Their structures were elucidated spectroscopically. To the best of our knowledge, all the compounds 1-5 were identified for the first time from the fruits of L. chinense.